A perfectionism, mental health and vulnerability to injury in triathletes - Gil-Caselles, Laura; Barquín, Roberto Ruiz; Gimenez-Egido, José María; García-Naveira, Alejo; Olmedilla, Aurelio (Frontiers in Psychology, 2025)
BackgroundTriathlon is a highly demanding and continuously growing sport in continuous growth. Due to its complexity, it often exposes the triathlete to a mental and physical load that is difficult to manage and exposes the athlete to sporting injury. Many triathletes are increasingly developing problems related to mental health and because of this, a greater vulnerability to suffer a sports injury is being observed.MethodsThe study sample included 172 triathletes (66.27% men, 33.72% women) categorized as Amateur, Youth, or Elite. Mean age: Amateur 40.19 ± 8.35, Youth 19.50 ± 2.63, Elite 30.38 ± 8.77. Weekly training: Amateur 5.63 ± 1.07 h, Youth 5.52 ± 1.28 h, Elite 6.58 ± 0.67 h. Daily training: Amateur 2.16 ± 1.66 h, Youth 2.38 ± 2.12 h, Elite 3.02 ± 2.00 h. Data collection involved administering a questionnaire assessing personal and sports-related variables, injury history, and mental health indicators. The psychological assessment included the Multidimensional Perfectionism Scale (MPS), the Depression, Anxiety, and Stress Scales (DASS-21), and the Profile of Mood States (POMS). The study design is descriptive-cross-sectional and has a retrospective character.ResultsSignificant positive correlations were found between TNL and TGSP across participants level, with the strongest correlation observed among youth athletes. Maladaptive perfectionism exhibited a weak negative correlation with TGSP in amateur athletes. Additionally, depression and stress were positively associated with TNL and TGSP, particularly in elite and youth athletes. Emotional state analysis showed that tension and depression were positively correlated with TNL and TGSP, whereas vigor was negatively correlated in elite athletes.ConclusionThese findings suggest a significant relationship between mental health and sports injuries, indicating that psychological distress not only contributes to injury risk but may also prolong recovery time in triathletes.